MENALAR PENTINGNYA PERAN MORAL VALUE BAGI HAMBA TUHAN DARI KERENTANAN DOSA SEKSUAL DI LINGKUP PELAYANAN GEREJA PENTAKOSTAL - Bunawan, Fernando (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
The Bible has provided guidelines regarding the importance of moral values ​​for God's servants in serving. Unfortunately, on many occasions there are still servants of God who behave badly, thus embarrassing and hurting themselves, their families, the church community, and even embarrassing and hurting God's heart. Immoral acts of God's servants like this also occur in the Pentecostal church. This research aims to explain the importance of the role of moral values ​​for God's servants from attacks by sexual sin in the scope of Pentecostal church services. This article discusses the Bible's description of the vulnerability of sexual sin, sexual sin in the scope of Pentecostal church services, as well as the importance of moral values ​​for God's servants. It is concluded that moral values ​​are important for servants of God in the scope of Pentecostal church service because they will be the protection that protects them from attacks by sexual sin, as a compass in ministry, the means that God uses to continue to exist in ministry, and they will leave a good legacy for the next generations.